FGF signaling is required for anterior but not posterior specification of the murine liver bud. Issue 3 (23rd October 2014) - Wang, Jikui; Rhee, Siyeon; Palaria, Amrita; Tremblay, Kimberly D.; Trainor, Paul; Johnson, Randy
<x xml:space="preserve">Abstract</x> Background: The definitive endoderm arises as a naive epithelial sheet that produces the entire gut tube and associated organs including the liver, pancreas and lungs. Murine explant studies demonstrate that fibroblast growth factor (FGF) signaling from adjacent tissues is required to induce hepatic gene expression from isolated foregut endoderm. The requirement of FGF signaling during liver development is examined by means of small molecule inhibition during whole embryo culture. Results: Loss of FGF signaling before hepatic induction results in morphological defects and gene expression changes that are confined to the anterior liver bud. In contrast the posterior portion of the liver bud remains relatively unaffected. Because FGF is thought to act as a morphogen during endoderm organogenesis, the ventral pancreas was also examined after FGF inhibition. Although the size of the ventral pancreas is not affected, loss of FGF signaling results in a significantly higher density of ventral pancreas cells. Conclusions: The requirement for FGF‐mediated induction of hepatic gene expression differs across the anterior/posterior axis of the developing liver bud. These results underscore the importance of studying tissue differentiation in the context of the whole embryo. Developmental Dynamics 244:431–443, 2015. © 2014 Wiley Periodicals, Inc.